A study on the impacts of continuous cropping on some soil indicators properties for the period 2017 to 2024 in Bazian Plain, Sulaimaniyah governorate, Iraq. - Akram M. Abdulrahman (Journal of Kerbala for Agricultural Sciences, 2025)
Continuous cultivation significantly impacts soil health, altering its physical and chemical properties, which are critical for sustainable agriculture. This study evaluates the effects of long-term agricultural practices in the Bazian Plain, Sulaimaniyah Governorate, Kurdistan Region, focusing on key soil properties across ten locations over the period 2017–2024. Soil samples were collected annually from greenhouses following standardized agricultural practices, emphasizing the cultivation of the cucumber variety A1. Key soil parameters analyzed include bulk density, permeability, porosity, organic matter, and root and shoot system distributions. Results indicate a progressive increase in bulk density, particularly in Latif Awa and Kani Big, reaching critical values of 1.48g.cm-3 by 2024, which reflect compaction due to continuous tillage. Permeability and porosity declined across all sites, limiting water infiltration and root penetration. Organic matter content decreased significantly, with Warmizyar and Zeika experiencing reductions to critical levels of 1.93% and 2.08%, respectively, indicating severe nutrient depletion. Root and shoot systems were notably reduced, with Kani Big showing the most pronounced decline in root length from 268 cm in 2022 to 211 cm in 2024.